PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 4 SUNGAI SIPUT KECAMATAN SIAK KECIL - Ruslan Zani; Lazim N Lazim N; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract: This research is motivated by the poor result of students mathematic learning.This can be seen from the value obtained by the student. Of the 19 students only 8 students (42,10%), which reached KKM specified school is 63, while 11 students (57,90%) did not reach the KKM. With the value of the average grade 60,90. According to this problem, the researchers have conducted research using research method class action (PTK) by applying cooperative learning model assisted individualization (TAI) tipe. At the first meeting of cycle one of teacher activity percentage 58,33% with enough categories, at the second meeting increased to 66,66% in both categories. In the second cycle the firsrt meeting with a percentage of 75,00% both categories, at the second meeting increased to 83,33% wih very good categori. Students activity also increased, in the first cycle of the first meeting of the percentage of the students activity 58,33% enough categori. At the second meeting increased to 70,83% in both categories, the second cycle of the first meeting of students activity increased with the percentage of 79,17% both categorie and second meeting increased to 83,33% very good categori. The average students learning outcomes before the applycation is 60,79 increased to 71,05 in the first cycle and increased again reaching 77,63 in the second cycle. Whereas classical to finish untill the end of the second cycle to complete the percentage achieved by the end of the classical 89,47 % with the number of students who completed 17 students out of students.Key Words: Cooperatif model team assisted indivudualization (TAI) type, learning result of mathematic